Fail silence mechanism for dependable vehicular communications. (2017) - Almeida, JoÁ£o; Ferreira, Joaquim; Oliveira, Arnaldo S. R.
This paper presents a fault-tolerant architecture to improve the dependability of infrastructure-based vehicular networks. For that purpose, a fail silence enforcement mechanism for road-side units (RSUs) was designed, implemented and tested. Vehicular communications based on IEEE 802.11p are inherently non-deterministic. The presence of RSUs and a backhauling network, adds a degree of determinism that is useful to enforce real-time and dependability, both by providing global knowledge and by supporting the operation of collision-free deterministic MAC protocols. One of such protocols is V-FTT, for which the proposed mechanism was designed as a case study. Notice, however that this mechanism is protocol independent and can be adapted to any wireless communications system. The proposed technique is capable of validating a frame for transmission by identifying faults both in value and time domains. Experimental results show that the fail silence enforcement mechanism has low latency and consumes few FPGA resources.